2015
DOI: 10.1177/0020764015573085
|View full text |Cite
|
Sign up to set email alerts
|

Self-harm and ethnicity: A systematic review

Abstract: There are clear ethnic differences in self-harm and suicide, which may be affected by factors such as cultural pressures and prevalence of mental illness. An awareness of these differences is vital to help prevent further attempts of self-harm and suicide. Further research into differences between ethnic and cultural groups and self-harm continues to be important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 35 publications
1
44
1
1
Order By: Relevance
“…There is some evidence that rates of self-harm differ by ethnicity [18], however previous literature does not make it clear which direction such an association might be expected to be in. Rates have been found to be higher in some non-white ethnic-minority groups [18], including South Asian [19] and Black Caribbean [20] women, compared to the white population in other UK settings.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that rates of self-harm differ by ethnicity [18], however previous literature does not make it clear which direction such an association might be expected to be in. Rates have been found to be higher in some non-white ethnic-minority groups [18], including South Asian [19] and Black Caribbean [20] women, compared to the white population in other UK settings.…”
Section: Discussionmentioning
confidence: 99%
“…We also reported that younger individuals were more likely to be from black and minority ethnic (BME) groups than the over 25 age group; this may reflect population demographics which show a significant young BME population in Birmingham. Whilst BME groups may be less likely to self-harm or seek help despite increased incidences of mental illness [ 31 , 32 ], this may not reflect a young BME sample and there is evidence that some younger BME groups, such as Asian women, are at increased risk of self-harm [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has demonstrated that immigrants may be at a higher risk for suicidal behaviour [ 10 , 11 ]. Several authors have also suggested that suicide risk may vary among ethnic minorities [ 12 ], and they may have different and more specific risk factors for suicidal behaviour than the general population, such as acculturative stress [ 13 ]. As suggested by Wyatt and colleagues [ 13 ], acculturation (a process by which subjects acquire the attitudes, values, customs, beliefs, and behaviours of a different culture) may play a role in the development of a suicidal crisis among migrants and ethnic minorities, besides classical psychosocial and psychopathological risk and protective factors [ 13 ].…”
Section: Introductionmentioning
confidence: 99%